Risk factors associated with the occurrence of antibodies against Toxoplasma gondii and Neospora caninum in domiciled dogs in Northeastern Brazil - Dantas, Sabrina Barros Araújo; Fernandes, Annielle Regina da Fonsêca; Souza Neto, Orestes Luiz de; Mota, Rinaldo Aparecido; Alves, Clebert José; Azevedo, Sérgio Santos de (Semina: Ciências Agrárias, 2014)
The aim of this survey was to determine the occurrence of antibodies against Toxoplasma gondii and Neospora caninum and to determine the risk factors associated with seropositivity in domiciled dogs in the county of Patos, Paraíba state, Northeastern Brazil. One hundred seventy-three blood samples were collected from dogs attended at the Veterinary Hospital of the Federal University of Campina Grande (HV/UFCG), Campus of Patos, Paraíba, during February to October 2011. For the serological diagnosis of T. gondii and N. caninum infection the indirect fluorescent antibody test (IFAT) was used adopting as cut-off points the dilutions 1:64 (T. gondii) and 1:50 (N. caninum). Of the 173 dogs used 27 (15.6%) were seropositive for T. gondii, and 13 (7.5%) for N. caninum. Variables age from 13 to 48 months (OR = 3.90), age > 48 months (OR= 5.14) and mixed-breed dogs (OR = 3.12) were identified as risk factors associated with T. gondii seropositivity, and for N. caninum the variable access of the dogs to ponds (OR = 5.67) was identified as risk factor. T. gondii and N. caninum infections, detected by IFAT, are present in domiciled dogs in the county of Patos, PB, as well as based on the risk factor analysis it is recommended to avoid the access of dogs to ponds.